Heutagogy-Based Training Management: Self-Determined Learning for Adult Learners - Imsiyah, Niswatul; Sintiawati, Nani; Purnamawati, Frimha; Himmah, Irliana F (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2024)
Heutagogy-based training management emphasizes learner autonomy, adaptability, and self-motivation